Christian Gottfried Ehrenberg und die Biogeographie: Die russisch-sibirische Reise mit Alexander von Humboldt (1829): - Päßler, Ulrich (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2021)
AbstractThe Russian-Siberian journey, carried out with Alexander von Humboldt and Gustav Rose in 1829 coincided with a decisive phase in Christian Gottfried Ehrenberg’s scientific career. His field diary and the drawings he made on the trip document his intensified focus on the study of microorganisms. The numerous observations on plant and animal geography show how Ehrenberg tested a combination of micro- and macro-perspectives that would shape his research on infusoria in the following decades: In addition to the task of classification at the microscope, Ehrenberg carried out worldwide comparative research on the distribution of microorganisms.ResumenEl viaje a Rusia y Siberia de Christian Gottfried Ehrenberg en compañía de Alexander von Humboldt y Gustav Rose, realizado en 1829, coincidió con una fase decisiva en su carrera científica. Su diario y los dibujos realizados durante el viaje documentan una especial atención al estudio de los microorganismos. Las numerosas observaciones sobre la geografía de las plantas y los animales muestran cómo Ehrenberg ensayó una combinación de micro y macroperspectivas que daría forma a sus investigaciones sobre los infusorios en las décadas siguientes. Además de su labor de clasificación al microscopio, Ehrenberg llevó a cabo una investigación comparativa a nivel mundial sobre la distribución de los microorganismos.RésuméLe voyage en Russie et en Sibérie entrepris en 1829 avec Alexander von Humboldt et Gustav Rose coïncide avec une phase décisive de la carrière scientifique de Christian Gottfried Ehrenberg. Son carnet de voyage ainsi que les dessins réalisés par lui lors du voyage témoignent de l’intensification de son intérêt pour l’étude des microorganismes. Les nombreuses observations sur la géographie des plantes et des animaux font preuve de la façon dont Ehrenberg a testé d’adopter une combinaison de micro- et de macro-perspectives qui ont façonné ses recherches sur les infusoires dans les décennies suivantes: Outre la tâche de classification au microscope, Ehrenberg a mené des recherches comparatives mondiales sur la distribution et la dispersion des microorganismes.